A Systematic Review of Natural Additives for Product Safety and Nutritional Value - Megavitry, Rissa; Fachruddin, Ismi Irfiyanti (West Science Agro, 2025)
The utilization of natural additives in food processing has gained significant attention due to growing consumer demand for safe, nutritious, and clean-label products. This systematic review analyzed 30 studies from the Scopus database to evaluate the types, functions, and impacts of natural additives on food safety and nutritional value. Findings reveal that plant-based, animal-derived, and microbial-derived additives demonstrate strong antimicrobial, antioxidant, and nutrient-enhancing properties. Natural additives such as polyphenols, essential oils, and bioactive peptides effectively improve product safety by inhibiting microbial growth, reducing oxidation, and mitigating mycotoxins. They also contribute to nutritional fortification and functional health benefits. Despite challenges such as cost, regulatory compliance, and sensory acceptance, the adoption of natural additives presents significant opportunities for sustainable and health-focused food innovation. This review underscores the importance of further research to optimize extraction methods, develop synergistic formulations, and enhance consumer education.